The impostor phenomenon in general practice/family medicine residents in Central Portugal, in 2022 (Revista Portuguesa de Medicina Geral e Familiar, 2025)
Background:  The impostor phenomenon (IP) characterizes individuals unable to recognize their success, attributing it to luck or assuming it was a mistake. Mental health problems can then occur. IP is most frequent in individuals with high academic and professional success, such as medical students and health professionals.Aim: To determine the prevalence of IP among general practice residents in Central Portugal, from the 1st to the 4th year of residency, in 2022, and its association with gender, year of residency, distress, anxiety, depression, and satisfaction with the average mark of the residency.Methods: A cross-sectional observational study was performed in a convenience sample. The Centre of Portugal Board of Residency in Family Medicine sent an invitation to respond to a Google questionnaire with the CIPS and PHQ-4 scales and questions about gender, year of residency, and satisfaction with the average mark of the residency. Descriptive and inferential statistics were performed.Results: A sample of 62 (69.7%) of 89 participants was studied. 12.9% of respondents were experiencing few, 22.6% moderate, 43.5% frequent, and 21% intense impostor feelings, with females suffering significantly more from IP (p=0.036). The Spearman’s correlation between PHQ-4 and CIPS was very weak and not significant (ρ=0.085, p=0.511).Discussion: With no other Portuguese data to compare with the present ones, possible explanations for a low response rate can have to do with fear of suffering IP, fear of showing the sufferance of IP, and answering the questionnaire and not sending it for fear.Conclusion: IP with a score at or above moderate has been detected in 87.1% of the residents. Women are more affected. No correlations were discovered between IP, distress, year of residency, and satisfaction with the average of the residentship. There is a need to recognize and manage IP, at both individual and institutional levels.